Admission outcomes and their associated factors among children admitted to the paediatric emergency unit within 24 hours of Dilla University Referral Hospital, Ethiopia, 2023: a cross-sectional study - Binyam Tariku Seboka; Tomas Yeheyis; Yihenew Ayehu Dessie; Samuel Jigso Dube; Abel Desalegn Demeke; Mekdes Mekonnen Feleke; Abdo Hajo Jarso; Asresu Feleke Bati; Etaferaw Udo; Selam Tadele Markos; Chalachew Kassaw; Amdehiwot Aynalem Debebe; et al. (BMJ Open)
Background Children in paediatric emergency units are those who need special attention, and unless treated early, they are a vulnerable population to unwanted outcomes like death, discharge against medical advice or referral to other institutions within 24 hours.Objectives To assess admission outcomes and their associated factors among children admitted to the paediatric emergency unit of Dilla University Referral Hospital, Ethiopia, 2023.Methods An institution-based cross-sectional study design was employed among children admitted to the paediatric emergency unit at Dilla University Referral Hospital from 8 May 2023 to 8 June 2023. A total of 885 complete charts of the children aged 29 days to 14 years were analysed. Structured checklist was used for data collection. STATA V.14 was used for data analysis. A multinomial logistic regression model was used to determine the factors associated with admission outcomes. Overall model fitness was checked using the likelihood ratio test.Result Out of 885 patient charts reviewed, the magnitude of patients improved, transferred, died, referred and discharged against medical advice was 51%, 40.9%, 7.6%, 0.1% and 0.4%, respectively. Children presented with diarrhoea (adjusted OR (AOR) =2.92, 95% CI 1.46 to 5.84), severe respiratory distress (AOR=5.08, 95% CI 2.49 to 10.35), coma (AOR=3.71, 95% CI 1.24 to 11.13), comorbidity (AOR=3.33, 95% CI 1.49 to 7.41) and delay to seek healthcare (AOR=1.99, 95% CI 1.03 to 3.83) were significantly associated factors with emergency unit mortality, whereas pneumonia (AOR=1.76, 95% CI 1.16 to 2.65) and severe acute malnutrition (AOR=3.46, 95% CI 2.06 to 5.81) were significantly associated factors with intrahospital unit/ward transfer.Conclusion The magnitude of mortality, transfer to the ward and discharge against medical advice were relatively higher. Interventions focused on early diagnoses, and the initiation of appropriate treatments was of the utmost relevance to improving patient outcomes.